George H. Ryden, Delaware - The First State in the Union 117 (1938) - (:unkn) unknown (My University, 1741)
Required males from 17 to 50 years to enlist. Besides that, everyone else who was living self-sufficiently (" every Freeholder and taxable Person" ) had to have the same arms as militiamen.
Keywords: MILITIAS; REQUIRED POSSESSION